49‐3: Late‐News Paper: Hybrid Capacitor Type Organic Electrochromic Device for Multicolor Representation. Issue 1 (25th September 2020) - Liang, Zhuang; Nakamura, Kazuki; Kobayashi, Norihisa
Abstract : In this paper, we designed a novel multicolor electrochromic (EC) device having hybrid capacitor electrochromic device based on 4, 4 '‐biphenyl dicarboxylic acid diethyl ester and phenothiazine molecule with carbon electrode. The EC properties of the device were analyzed and discussed for the possibility to multicolor representation.